Preparation And Properties Of Biodegradable Polymer Blended Film Based On Polyvinyl Alcohol And Tropical Fruit Waste Flour - Ooi, Zhong Xian (2011)
In this study, a new polymer blends by blending tropical fruit waste flour with polyvinyl alcohol (PVOH) using solution casting method was prepared and examined. Firstly, the rambutan waste flour (RWF) was selected to blend with PVOH. Plasticized biodegradable PVOH/RWF films at different weight ratio of PVOH and RWF content were developed and thus effect of plasticizing agents on the properties of resulting films was evaluated. Results showed that the glycerol-plasticized films exhibited higher elongation at break, but lower tensile strength and Young’s modulus than that of sorbitol-plasticized films, which mainly due to the better plasticizing effect of glycerol.